Freeze-dried strawberry and blueberry attenuates diet-induced obesity and insulin resistance in rats by inhibiting adipogenesis and lipogenesis. Issue 11 (12th October 2017) - Aranaz, Paula; Romo-Hualde, Ana; Zabala, María; Navarro-Herrera, David; Ruiz de Galarreta, Marina; Gil, Ana Gloria; Martinez, J. Alfredo; Milagro, Fermín I.; González-Navarro, Carlos J.
Abstract : Freeze-dried strawberry/blueberry powder might be useful for treatment/prevention of obesity-related diseases as it improves weight, fat and glucose-related biomarkers. Abstract : Obesity and type 2-diabetes are becoming a worldwide health problem, reiterating the importance of alternative therapies to tackle their progression. Here, we hypothesized that supplementation of diet with 6% w/w of a freeze-dried strawberry–blueberry (5 : 1) powder (FDSB) could exert beneficial metabolic effects on Wistar rats. FDSB-supplemented animals experienced significantly reduced body weight gain, food efficiency and visceral adiposity accumulation in two independent experiments. FDSB supplementation also contributed to lower area under the curve after an intraperitoneal GTT and reduced serum insulin levels and an insulin resistance index (IR-HOMA) in HFS diet-fed animals, together with reduced plasma MCP-1 inflammation marker concentrations. Gene expression analysis in retroperitoneal adipocytes from experiment 1 and 3T3-L1 cells showed that FDSB inhibited adipogenesis and lipogenesis through down-regulation of Pparg, Cebpa, Lep, Fasn, Scd-1 and Lpl gene expression. Untargeted metabolomics identified the cis isomer of resveratrol-3-glucoside-sulphate as a metabolite differentially increased in FDSB-treated serum samples, which corresponds to a strawberry metabolite that could be considered a serum biomarker of FDSB-intake. Our results suggest that FDSB powder might be useful for treatment/prevention of obesity-related diseases.